Revisiting the connectivity puzzle of the common coral Pocillopora damicornis. Issue 23 (7th November 2013) - Torda, G.; Lundgren, P.; Willis, B. L.; van, M. J. H.
Abstract Understanding levels of connectivity among scleractinian coral populations over a range of temporal and spatial scales is vital for managing tropical coral reef ecosystems. Here, we use multilocus microsatellite genotypes to assess the spatial genetic structure of two molecular operational taxonomic units (MOTUs, types α and β) of the widespread coral Pocillopora damicornis on the Great Barrier Reef (GBR) and infer the extent of connectivity on spatial scales spanning from local habitat types to latitudinal sectors of the GBR. We found high genetic similarities over large spatial scales spanning > 1000 km from the northern to the southern GBR, but also strong genetic differentiation at local scales in both MOTUs. The presence of a considerable number of first‐generation migrants within the populations sampled (12% and 27% for types α and β, respectively) suggests that genetic differentiation over small spatial scales is probably a consequence of stochastic recruitment from different genetic pools into recently opened up spaces on the reef, for example, following major disturbance events. We explain high genetic similarity among populations over hundreds of kilometres by long competency periods of brooded zooxanthellate larvae and multiple larval release events each year, combined with strong longshore currents typical along the GBR. The lack of genetic evidence for predominantly clonal reproduction in adult populations of P. damicornis, which broods predominantly asexually produced larvae, further undermines the paradigm that brooded larvae settle close to parent colonies shortly after the release.